Pemanfaatan Aplikasi Telegram untuk Meningkatkan Kompetensi Guru dalam Pembuatan Bahan Ajar Video Menggunakan Smartphone - Mamat Mamat; Amar Nugraha (Jurnal Didaktika Pendidikan Dasar, 2022)
This study explores the use of the Telegram application to increase teacher competence in making video teaching materials using smartphones or smartphones. This study aims to improve understanding and development of technology for educators and education personnel in making teaching videos using smartphones. The subject of this case study is the Telegram group account "Technology Literacy Teacher" which has a group of 4,720 members from all over Indonesia. The method used is a qualitative approach and data is collected through participatory analysis. The researcher participates in becoming a member of the Telegram group. The results of the study found that there was an increase in the motivation and the ability of participants in making video learning materials.